ANALYSIS OF CURRENT RATIO CHANGES EFFECT, ASSET RATIO DEBT, TOTAL ASSET TURNOVER, RETURN ON ASSET, AND PRICE EARNING RATIO IN PREDICTINGGROWTH INCOME BY CONSIDERING CORPORATE SIZE IN THE COMPANY JOINED IN LQ45 INDEX YEAR 2013 -2016 - Wikan Budi Utami (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
This study aims to determine the effect of the partially and simultaneously of the Current Ratio (CR), Debt Asset Ratio (DAR), Total Asset Turnover (TATO), Return On Assets (ROA), and Price Earning Ratio (PER) in predicting profit growth by considering firm size at company incorporated in LQ45 index year 2013 -2016 with company size as control a variable. The technique of determining the sample in this research is by using purposive sampling. There are several criteria that must be met by companies listed in the LQ45 Index to be sampled in this study. This research method is using multiple regression analysis which is used to know the influence of independent variable to the dependent variable together and partially. The t test is used to test the influence of each variable change Current Ratio, Debt Asset Ratio, Total Asset Turnover, Return On Asset , and Price Earning Ratio to earnings growth variable with firm size as control variable. The statistical test F aims to examine the effect of changes in Current Ratio, Debt Asset Ratio, Total Asset Turnover, Return On Asset, and Price Earning Ratio simultaneously to the variable of profit growth with firm size as control variable. The R2 test (Coefficient of determination) is done to find out how big the influence variable change Current Ratio, Debt Asset Ratio, Total Asset Turnover, Return On Asset, and Price Earning Ratio to variable growth profit with company size as control variable. From result of t test is known that change of Total Assets Turn Over and change of Return On Assets partially have significant effect to profit growth (∆ EAT) .Variable change of Curent Ratio (∆CR), change of Debt Asset Ratio (∆ DAR), Price Earning Ratio (∆PER) partially no significant effect on profit growth variable with firm size as control variable. From result of F test, it is known that Current Ratio (∆ CR) change, Debt Asset Ratio (Δ DAR) change, Total Asset Turnover (∆ TATO), Return On Asset (∆ ROA) change, Price Earning Ratio (∆ PER) simultant significant effect on profit growth variable at go public company listed in index LQ 45 in Indonesia with company size) as control variable. Keywords: Change of CR, DAR, TATO, ROA, PER, Profit Growth.